Memahami Peserta Didik Melalui Prinsip-Prinsip Kepribadian - Lastiur Monica Munthe; Dorlan Naibaho (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The purpose of this writing is to increase understanding of how the principles of student personality can be utilized in an educational context, using a descriptive qualitative approach. This approach involves collecting data from libraries or scientific journals to ensure the information obtained is in-depth and verified. The main focus of the research is to describe and analyze how teachers integrate a deep understanding of students' personalities in the teaching process. The findings of this research provide insight into the potential of applying personality principles as an effort to improve the overall learning experience and strengthen interpersonal relationships in educational environments. The results of this research can provide valuable guidance for educational practitioners who wish to optimize learning through better understanding of students.